Association between pregnancy and severe COVID-19 symptoms in Qatar: A cross-sectional study. - Alla' K Al-Qassem; Ammar B Humaidi; Amna K Al-Kuwari; Elham M Hasan; Nosaiba H Yakti; Rakan M Al-Hathal; Devendra Bansal; Elmoubashar Abu Baker Abd Farag; Hamad E Al-Romaihi; Mohammed H J Al-Thani; Omran A H Musa; Suhail Doi; et al. (PLOS Global Public Health, 2023)
There is inconclusive evidence whether pregnancy exacerbates COVID-19 symptoms or not, and scarce data from the Middle East and North Africa region. The aim of this study was to investigate the association between pregnancy and COVID-19 symptoms in Qatar. This cross-sectional study was carried out using data of all women with confirmed COVID-19, comparing women of child-bearing age (18-49 years). Data of all COVID-19 cases were collected by the Ministry of Public Health (MoPH) in Qatar, between March and September 2020. Symptoms were compared by pregnancy status and classified into moderate and severe. Multivariable logistic and Poisson regression was carried out to investigate the association between pregnancy and severity of COVID-19 symptoms. During the study period, 105 744 individuals were diagnosed with COVID-19, of which 16 908 were women of childbearing age. From that sample, 799 women were pregnant (mean age 29.9 years (SD 5.2)) and 16109 women were not pregnant (mean age 33.1 years (SD 7.8)). After multivariable logistic regression, pregnancy was associated with 1.4-fold higher odds of reporting any symptoms of COVID-19 (OR 1.41, 95% CI 1.18-1.68), and 1.3-fold higher odds of reporting shortness of breath (OR 1.29, 95% CI 1.02-1.63). In a multivariable Poisson regression, pregnancy was also associated with a higher count of symptoms (IRR 1.03, 95%CI 0.98-1.08), although with weak evidence against the null hypothesis. Our findings suggest that, in this setting, pregnant women are more likely to have symptomatic COVID-19, and shortness of breath, compared to women with no pregnancy.